2-Chloro-N-(4-fluorophenyl)acetamide - Kang, Si-shun (International Union of Crystallography, 2008)
In the title compound, C(8)H(7)ClFNO, an intramolecular C—H⋯O hydrogen bond forms a six-membered ring. In the crystal structure, molecules are linked by intermolecular N—H⋯O hydrogen bonds, forming infinite chains along the c axis.